How May the Increase in Pink Salmon (Oncorhynchus gorbucsha) Cause the Populations of the Atlantic Salmon (Salmo salar) to Decline? - Keinänen, Marja; Vuorinen, Pekka Juhani (MDPI, 2025)
Atlantic salmon (Salmo salar) populations in the Arctic River Teno (Tana) and other North Atlantic rivers have declined at the same time as pink salmon (Oncorhynchus gorbuscha) have begun to spawn extensively in these rivers in odd-numbered years. In the River Teno, especially, the number of one-sea-year Atlantic salmon ascendants has decreased. In this short review, we assess, based on current information, how the abundance of pink salmon may weaken the survival of Atlantic salmon. Our hypothesis is based on recent evidence from Atlantic salmon in the Baltic Sea showing that the high marine lipid content in the diet of Atlantic salmon post-smolts impairs their growth and survival and is manifested in low numbers of ascendants and in poor thiamine (vitamin B1) status in both juvenile and spawning Baltic salmon. The high energy density of lipids increases the need for thiamine in the metabolism, and the high content of highly unsaturated fatty acids (n–3 HUFAs), like docosahexaenoic acid (DHA, 22:6n–3), in marine fish lipids increases the rate of lipid peroxidation, which consumes thiamine as it acts as an antioxidant against lipid peroxidation. The review presents information that could be used in planning possible future research on the topic.
Keywords: rasvahapot; Fatty Acids; lohikalat; atlantinlohi; eggs; Atlantic salmon; lipid content; Thiamine Deficiency; thiamin; pink salmon (Oncorhynchus gorbuscha); post-smolt survival; n–3 HUFAs; dietary energy density; River Teno; tiamiini; Salmoniformes; early developmental phases; Atlantic salmon (Salmo salar)